Peningkatan Kemampuan Memukul Bola Pada Permainan Rounders Melalui Modifikasi Bolagantung Pada Siswa Kelas V SD Negeri Bulusari 1 Kecamatan Tarokan Kabupaten Kediri Tahun 2024/2025 - Ahmad Suhadak; Wasis Himawanto; Dwi Sulistyo Nugroho (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to improve student learning outcomes in the subject of Physical Education, Sports, and Health in grade V students of SD Negeri Bulusari 1, Kediri Regency through the application of the play group method. This study uses the Classroom Action Research (CAR) approach which is implemented in two cycles. Each cycle consists of the stages of planning, action implementation, observation, and reflection. The subjects of the study were all grade V students of SD Negeri Bulusari 1, Tarokan District, Kediri Regency.Based on the observation results in cycle 1, out of 14 fifth grade students of SD Negeri Bulusari 1, there were 5 students who were able to hit the ball correctly. Students are declared to be able to hit the ball correctly if they are able to hit the ball correctly 3 times out of 5 times hitting the ball. During the learning process in cycle 1 related to student attitudes, the percentage results were 68.6%, while the target desired by the researcher was that at least 80% of the number of students must achieve the Minimum Completion Criteria (complete) value. The ability of students to hit the ball in cycle 2 increased from cycle 1, this is indicated by the decrease in the number of students who were able to hit the ball less than 3 times out of 5 times hitting the ball. During the learning process in cycle 2 related to student attitudes, it increased to 91.5% (up 22.9% from cycle 1). This success rate indicates that the learning process of the rounders game with this modification was successful because it had reached the target and even exceeded the target desired by the researcher, namely 80% of the number of students had completed the Minimum Completion Criteria value.Learning the rounders game with modifications received positive responses from students. This can be seen from the results of the student response questionnaire analysis of learning the rounders game with modifications which showed that almost 90% of students felt happy in following the learning process. So it can be concluded that learning the rounders game with modifications is acceptable and can improve student learning outcomes.